PENERAPAN MODEL PEMBELAJARAN KOOPERATIF PENDEKATAN STRUKTURAL NUMBERED HEADS TOGETHER (NHT) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VIII6 SMP NEGERI 12 PEKANBARU - Nasuha, Siti; ', Jalinus; Anggraini, Rini Dian (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: this research is motivated by the result of learning mathematics of class student VIII6 SMP Negeri 12 Pekanbaru which is still under the minimum mastery criteria with a persentage of 37,5% only 15 students from 40 students who achieve the minimum mastery criteria on the subject matter of the circle. The purpose of this study is to improve the learning process and increase the student?s mathematics learning outcomes through the implementation of Cooperative learning structured approach Numbered Heads Together. This type of research is the Classroom Action Research with two cycle. The research was conducted in class VIII6 SMP Negeri 12 Pekanbaru in the second semester of the 2016/2017 academic year with the subject of as many as 40 students, consist of 22 boys and 18 girls. The research instrument consists of learning devices and instrument data collectors. Learning device used in this research is the Syllabus, Lesson Plan and Worksheet. The instrument data collector used in this research is the observation sheet and math achievement test. The observation sheet was analyzed descriptive qualitative while the test of mathematics learning outcomes was analyzed statistically. Based on qualitative analiysis showed that implementation of learning process on cycle II had happened improvement from implementation on cycle I. Weakness on cycle I is improved on implementation cycle II according with planning of improvement after reflection cycle I. Number of students that reach Minimum Mastery Criteria increase from basic score to daily test II. The number of students who reach Minimum Mastery Criteria on basic scor, daily test I and daily test IIare respectively 15 person (37,5%), 20 person (50%) and 27 person (67,5%). Results of this research indicates that application of the Cooperative learning structured approach Numbered Heads Together can improve learning process and increase mathematics learning outcomes from the students at class VIII6 SMP Negeri 12 Pekanbaru in the second semester academic years 2016/2017.Key words: Students? Math Achievement, Cooperative Learning Structural Approach ofNumbered Heads Together, Classroom Action Research.